Quality of different tropical fruit cultivars produced in the Lower Basin of the São Francisco Valley - Batista, Patrício; Lima, Maria Auxiliadora; Trindade, Danielly Cristina; Alves, Ricardo (Revista Ciência Agronômica, 2014)
The present study evaluated the physical, physico-chemical and chemical characteristics of fruit from commercial cultivars of the mango, acerola, guava, atemoya and custard apple, produced in the Lower Basin of the São Francisco Valley. Fruit harvested in commercial areas of the region were evaluated for weight, length, diameter, colouration of the peel and pulp, firmness, pH, titratable acidity (TA), soluble solids (SS), SS to TA ratio, and levels of total soluble sugars, reducing sugars, starch and pectic substances. The data were subjected to descriptive statistical analysis. Fruits from cultivars of the guava (Paluma, Rica and Pedro Sato), the custard apple and atemoya display a high level of pectic substances, a characteristic which favours industrial use. In the mango, a high level of pectic substances was noted in fruit of the cultivars Kent, Espada, Tommy Atkins and Van Dyke. Fruits of the acerola cultivar Costa Rica show high SS content and a low AT, favouring consumption in natura.